Development of a group guidance model based on polibu ntodea culture to improve tolerance values among students - Ema Hardiana; Abdullah Sinring; Sulaiman Samad (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to: (i) obtain a description of the need to develop a group guidance model based on Polibu Ntodea to increase tolerance values among students; (ii) yield a description of the prototype of a group guidance model based on Polibu Ntodea that can increase tolerance values among students; and (iii) determine the validity and practicality of a group guidance model based on Polibu Ntodea that can increase tolerance values among students. This study adopted the 5-step Borg & Gall research and development model. The subjects of the study were seven students of SMAN (State Senior High School) 4 Sigi in the odd semester of the academic year 2021/2022, selected using the purposive sampling technique. In this study, both qualitative and quantitative approaches were used for the analysis. The results of the study showed that: (i) the development of a group guidance model based on Polibu Ntodea was very necessary to increase tolerance values among students; (ii) this study yielded a product, which is a group guidance model based on Polibu Ntodea that can increase tolerance values among students; and (iii) a group guidance model based on Polibu Ntodea was very useful, feasible, appropriate, and practical to use to increase tolerance values among students